Analisis Perilaku Bullying Siswa di Sekolah - Ruswita, Nanda; Yandri, Hengki; Juliawati, Dosi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
The background of this research is that nowadays we were still found some students who still do some bullying at school, so the purpose of this study is to reveal the intensity of student bullying behavior in schools related to 1) physical bullying, 2) verbal bullying, 3) relational bullying, 4) cyberbullying. This research is a quantitative descriptive study with 30 students as respondents. Data was collected through a questionnaire and analyzed using the ideal score formula. The results of this research study is indicate that the average of the respondent has an intensity of bullying behavior in the medium category.